Optimizing qubit performance through smoothing techniques - Ivan P. Malashin; Igor S. Masich; Vadim S. Tynchenko; Aleksei S. Borodulin (Scientific Reports)
Abstract This study explores an approach to enhance the performance of qubits by leveraging signal smoothing algorithms applied to qubit chips. The primary aim is to mitigate experimental variability and enhance overall stability, tied to the improvement of the Hamiltonian spectrum. By optimizing qubit operation through smoothing techniques, data processing for subsequent stages of two-tone qubit spectroscopy data transformation is facilitated. Specifically, through the subsequent pipeline of calibration transformations for resonator frequency, qubit frequency, qubit amplitude calibrations, and refinement of qubit frequency via Ramsey oscillations, qubit state calibration can be achieved. This, in turn, improves qubit coherence time during measurement. This is because smoothing allows for a more precise determination of the Hamiltonian spectrum on two-tone spectroscopy maps, thereby enabling more accurate parameter construction.